726 Our gratitude and appreciation for your feedback. (24th April 2018) - Howard, AM; Harrison, C
Abstract : Introduction: In May 2017 the Occupational Health Safer Better Care Standards were launched. Standard 1.4 of the Occupational Health, Safer Better Care Standards states' Workers feedback including complaints and compliments are responded to promptly, openly and effectively with clear communication and support provided throughout this process' Method: On an ongoing basis in Occupational Health we have a suggestion box in our four Occupational Health Departments for feedback. In our work plan for 2017 we had decided to dedicate the month of May to doing a client satisfaction survey. The survey questionnaire is based on the validated national occupational service patient survey in the National Health Service UK (NHS). We decided as a team that each of the four Occupational Health units in the South East would hand this survey to clients who pass through their departments in the month of May. In addition Ann Marie Howard, CNM3 asked the Occupational Health staff to send her any Thank you cards they had received. Ann Marie met with Ciara the Artist in residence in Waterford and discussed ideas with her in relation to what we could with the Thank you cards and feedback cards kindly received. It was decided we would do a calendar for 2018 and call it' Occupational Health- Our Gratitude and Appreciation for your feedback'. We decided to use a theme for each month for example January and July are the months where you have new Junior Doctors, September is a month when you have an intake of student nurses and October is the month for Influenza vaccination. Along with the theme for each month we are taking words, sentence clients wrote in there Thank you cards and Feedback and illustrate them throughout the calendar. Results: The Thank you cards and feedback cards have all been collected. The May 2017 client satisfaction survey has yet to be analysed and results written up. It is a work in progress. Discussion: Our hope would be we will get the calendar published and communicate it to all client users as a feedback mechanism on our gratitude and appreciation. Following on from this project it would be a wonderful addition if an app could be developed for Occupational Health as a communication tool.